Evidence of cationic Pt active for water-gas shift reaction: Pt-doped BaCeO3 perovskite - Rajesh, Thattarathody; Rajarajan, Anakot K.; Gopinath, Chinnakonda S.; Devi, R. Nandini (Journal of Physical Chemistry C, 2012)
Precious metal incorporated into stable lattices like perovskites can be envisaged as an alternative catalysts to address deactivation problems. Here we report the barium cerate perovskite doped with varying amounts of Pt as catalysts for the water-gas shift reaction whereby ionic Pt is evidenced to be active. It is found that maximum CO conversion occurs above 325 degrees C and increases more than 2-fold after the first cycle. XPS analysis shows that after the first cycle, more ionic Pt species are present on the surface of the catalyst. X-ray and neutron diffraction studies also indicate the presence of oxygen vacancies that increases with increasing Pt substitution.